OPERATIONAL RISK MANAGEMENT IN THE CIBITUNG METLAND WATERLAND BUILDING ON INVESTMENT COSTS - Patrick Sudiarto; Fitri Suryani; Arman Jayady (International Journal Labs, 2022)
Developer policy in this case PT. Metropolitan land, Tbk for the availability of entertainment facilities in the region is the right choice to increase profits in addition to selling home products. This strategy is considered appropriate because of the lack of entertainment in the area around housing which is seen from the rapid population from year to year. Service providers bear a large risk burden at the operational stage, To avoid cost overrun, in the calculation of the operating cost budget it is necessary to include costs due to risks. Risk costs are allocated to the identified risks. This study aims to identify the dominant risk factors that affect operational investment costs from the point of view of other long-running operational management. The research used qualitative methods when conducting studies on previous research which then obtained 48 risk factors that affect investment costs. Validation of the 48 risk factors was carried out by 3 (three) experts and produced 30 risk variables which then became questionnaires that would be distributed to respondents. Quantitative methods are used to assess probability and impact using a rating scale. The probability and impact values are converted into values in the probability-impact matrix, after the risk value is calculated and sorted from the highest value, 4 dominant risk factors are obtained, namely, Leaking on the walls and floor of the pool, Damage to playgrounds, Damaged plumbing systems, and Pumping machines are off or damaged.